Sistem Administrasi Keuangan Pada Masjid At-Taqwa Desa Pasar Singkut - Frendy, Ahmad; Riza Pahlevi; Masgo (LPPM Universitas Dinamika Bangsa, 2025)
At-Taqwa Mosque is a place of worship for Muslims. In processing the cash data, there are problems because the mosque's cash bookkeeping still uses paper so that damage or loss of data can occur and can only be accessed by one person. The data search process takes a long time because cash data is written into the book. Experiencing difficulties in making reports. The purpose of this study is to analyse the current system, in order to overcome the problems faced at the At-Taqwa Mosque, by designing a Web-Based At-Taqwa Mosque Cash Data Processing System Design. The research framework that will be carried out in solving the problems discussed, namely, identifying, searching for information based on theoretical foundations, collecting data using observation and interview methods, analysing to find solutions to the problems faced by the At-Taqwa Mosque. The system development method uses the waterfall model, the implementation of this research uses the PHP programming language and MySQL DBMS. To produce data processing applications that are expected to facilitate data processing and report generation.